Hedonic prices and quality adjusted price indices powered by AI - Patrick L. Bajari; Zhihao Cen; Victor Chernozhukov; Manoj Manukonda; Jin Wang; Ramon Huerta; Junbo Li; Ling Leng; George Monokroussos; Suhas Vijaykunar; Shan Wan (Centre for Microdata Methods and Practice (cemmap), 2023)
Accurate, real-time measurements of price index changes using electronic records are essential for tracking inflation and productivity in today's economic environment. We develop empirical hedonic models that can process large amounts of unstructured product data (text, images, prices, quantities) and output accurate hedonic price estimates and derived indices. To accomplish this, we generate abstract product attributes, or "features," from text descriptions and images using deep neural networks, and then use these attributes to estimate the hedonic price function. Specifically, we convert textual information about the product to numeric features using large language models based on transformers, trained or fine-tuned using product descriptions, and convert the product image to numeric features using a residual network model. To produce the estimated hedonic price function, we again use a multi-task neural network trained to predict a product's price in all time periods simultaneously. To demonstrate the performance of this approach, we apply the models to Amazon's data for first-party apparel sales and estimate hedonic prices. The resulting models have high predictive accuracy, with R 2 ranging from 80% to 90%. Finally, we construct the AI-based hedonic Fisher price index, chained at the year-over-year frequency. We contrast the index with the CPI and other electronic indices.
Keywords: 330; Hedonic Prices; Price Index; Transformers; Deep Learning; Artificial Intelligence